Use of Embodied Conversational Agents to Engage Visitors in Art Exhibits - Ferreira Neto, José Fernando R.; Colares, Daniel M.; Ribeiro, Daniel; Fontes, Yuri Nekan S.; Pinheiro, Vladia (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37855, 2025)
The rapid advancement of Artificial Intelligence presents new opportunities and challenges across numerous fields. This paper explores the application of Embodied Conversational Agents in art galleries as a means to enhance visitor engagement. We propose a general system architecture for developing such an agent and describe the implementation of an interactive exhibit based on the painting ”Cabeça de Mulato” by Candido Portinari. Preliminary results from logged visitor interactions indicate that ECAs can indeed foster meaningful engagement in cultural settings.